Phylogenomic analysis of Picramnia, Alvaradoa, and Leitneria supports the independent Picramniales. Issue 3 (27th March 2017) - Logacheva, Maria D.; Shipunov, Alexey B.
Abstract: Picramniales is a recently established monotypic order that has not yet acquired a stable position on the phylogenetic tree of flowering plants. While Picramnia and Alvaradoa were transferred from Simaroubaceae (Sapindales) into Picramniaceae (Picramniales), Leitneria was transferred from the "hamamelids" into Simaroubaceae. Using next‐generation sequencing, we obtained plastome sequences of Picramnia and Alvaradoa (partial) and Leitneria (complete). Protein coding and rRNA genes common for flowering plant plastomes were used for phylogenetic analysis. The resulting phylogenetic trees demonstrate a robust placement of Picramniales among the rosids as a sister group to Sapindales + Brassicales + Malvales. Leitneria is placed as a sister to Citrus . We also found that the plastome of Leitneria carries ycf68 gene that is absent from most other rosids and infA pseudogene.